Respiratory quotient: Effects of fatty acid composition. Issue 9 (15th October 2020) - Price, Edwin R.; Mager, Edward M.
Abstract: Respiratory quotient (RQ) is commonly used to infer which substrates are oxidized, with glucose yielding RQ = 1 and fat normally thought to yield an average of RQ = 0.71. Because fat depot compositions differ among species, we examined how the various common fatty acids affect RQ. RQs ranged from less than 0.7 (e.g., stearic acid) to greater than 0.76 (e.g., docosahexaenoic acid). Furthermore, we conducted a survey of the fatty acid composition of fuel lipids of several vertebrate taxa to determine how the RQ for lipid oxidation during fasting should vary among species. Our survey indicates that most fasting vertebrates from terrestrial ecosystems oxidizing fat should have RQs equaling approximately 0.71, as normally expected. However, some fasting animals in aquatic or marine systems—particularly fish—should have RQs as high as 0.73 when oxidizing only fat. Selective mobilization of fatty acids increased the lipid RQ, but probably by a negligible amount. We conclude that researchers should take habitat and taxon into account when choosing a value for lipid RQ, and preferably should use fatty acid composition for their study species to determine an appropriate RQ for lipids. In the absence of species‐specific fatty acid composition data, we suggest assuming a lipid RQ of 0.725 for cold‐water fish. Abstract : Predicted respiratory quotient (RQ) for lipid oxidation for various species based on the fatty acid composition of their fuel lipids. Lipid RQ is approximately 0.715 for most mammals and birds but ranged as high as 0.73 for some fish. Highlights: The respiratory quotient (RQ) for lipids is generally assumed to be 0.71 and to vary little among animals. We conducted a survey of fatty acid composition of major vertebrate groups. RQ for lipids ranges as high as 0.73 in fish, suggesting that using 0.71 in calculations of fuel use can result in errors of up to 10%. xxx